Pre-operative Bronchodilator Treated Patients Preserve Better Pulmonary Function in CABG Cases (Journal of Surgical Sciences, 2019)
Background: Bronchodilator {P2selective adrenergic drug-salbutamol) causes bronchodilation and increases the vital capacity, tidal volume and total lung capacity and reduces gas trapping. Use of bronchodilator in patients undergoing Off-pump coronary artery bypass graft (OPCABG) may lead to better preservation of pulmonary function.Objective: To evaluate the role of bronchodilator on preservation of post-operative pulmonary function in patients who underwent OPCABG.Methods: This study was conducted on 50 patients randomized into two groups to assess the pulmonary function after off-pump CABG. Among them, 25 patients (group-I) were treated by preoperatively bronchodilator and compared them with other 25 patients (group-II) who were not treated by preoperative bronchodilator. We compared arterial blood gas analysis, duration of total mechanical ventilation, days spent in the surgical ICU and spirometric indices.Results: Mean±SE value of mechanical ventilation time after operation in group-I was 14.25±0.85 hours and in group-II was 16.88±0.85 hours. Mean±SE value of ICU stay after surgery was 98.64±2.07 hours in group I and 110.56±2.36 hours in group-II. Both results were statistically significant (P=0.042 and P=0.001 respectively). The FVC and FEV1 after admission were not statistically significant (P>0.05). On the day before surgery the values of FVC and FEV1 were increased (more in group-1 who were treated with bronchodilator) and 7th postoperative day the value were decreased (more in group -11 who were not treated with bronchodilator). The results were found statistically significant in between two groups (P